Vitamin B12 Reduces TDP-43 Toxicity by Alleviating Oxidative Stress and Mitochondrial Dysfunction - Yu-Mi Jeon; Younghwi Kwon; Shinrye Lee; Seyeon Kim; Myungjin Jo; Seongsoo Lee; Sang Ryong Kim; Kiyoung Kim; Hyung-Jun Kim (MDPI AG, 2021)
TAR DNA-binding protein 43 (TDP-43) is a member of an evolutionarily conserved family of heterogeneous nuclear ribonucleoproteins that modulate multiple steps in RNA metabolic processes. Cytoplasmic aggregation of TDP-43 in affected neurons is a pathological hallmark of many neurodegenerative diseases, including amyotrophic lateral sclerosis (ALS), frontotemporal dementia (FTD), Alzheimer's disease (AD), and limbic predominant age-related TDP-43 encephalopathy (LATE). Mislocalized and accumulated TDP-43 in the cytoplasm induces mitochondrial dysfunction and reactive oxidative species (ROS) production. Here, we show that TDP-43- and rotenone-induced neurotoxicity in the human neuronal cell line SH-SY5Y were attenuated by hydroxocobalamin (Hb, vitamin B12 analog) treatment. Although Hb did not affect the cytoplasmic accumulation of TDP-43, Hb attenuated TDP-43-induced toxicity by reducing oxidative stress and mitochondrial dysfunction. Moreover, a shortened lifespan and motility defects in TDP-43-expressing Drosophila were significantly mitigated by dietary treatment with hydroxocobalamin. Taken together, these findings suggest that oral intake of hydroxocobalamin may be a potential therapeutic intervention for TDP-43-associated proteinopathies.